Ifa divination trays from Isale-Oyo (2011)
This paper is a study of the images and patterns on ifa divination trays from Isale-Oyo. The paper also explains some ifa paraphernalia. The paper establishes that ifa trays from Isale-Oyo bear distinctive features when compared with other ifa trays in Yorubaland such as those of Ijebu and Osogbo. Central to this study is the monographic description and interpretations of Isale-Oyo divination trays. Data were collected through direct interviews with divination tray owners. Photographs of the trays were also taken. The investigation revealed that:• Divination trays from Isale-Oyo combine features found on both Ijebu and Osogbo trays.• The Esu figure continues to occupy the top central position on Oyo divination trays, even though with representational variations elsewhere in Yorubaland.• Some divination trays in Oyo carry no decorations on their borders, and in some recent cases, ceramic plates are now used for divination.